Corruption in college admissions examinations in China. (March 2015) - Liu, Qijun; Peng, Yaping
Highlights: Utilizing the data from a survey among college students of arts and related majors across China, this paper examines corruption in college admissions examinations. It is found that the objective level of corruption is 15.8 percent while the subjective level is 47.3 percent. Lack of transparency, poor design of the examinations, tolerance of corruption, high levels of corruption propensity and high income expectations in future careers are identified as the main causes of corruption. Corruption in the examinations leads to reduction of student trust in the accountability of faculty and staff in higher educational institutions. Abstract: This paper examines corruption in college admissions examinations in China. A survey was administered among college students of arts and related majors across China. Based on the data, the magnitude of corruption in the admissions examinations is measured and the causes and consequences thereof are investigated. It is found that the objective level of corruption is 15.8 percent while the subjective level is 47.3 percent. Lack of transparency, poor design of the examinations, the subjects' tolerance of corruption, high levels of corruption propensity, and high income expectations in future careers are identified as the main causes of corruption. Corruption in the examinations lowers student trust in the accountability of faculty and staff in higher educational institutions and this degrading trust in turn exacerbates bribery among new generations of examinees, which results in a vicious cycle of corruption.